Indisciplina em sala de aula - Valentim, Lenira Maria (2016)
This work deals with the theme of "indiscipline in the classroom," whose focus is to analyze the causes and consequences of the aggressive behavior of most students seeking educational alternatives and even family solutions. We also highlight some authors who contributed quite enlightening content on this theme; Parrat (2012), Luengo (2010), Tiba (2006), Shinyashiki (2011), Oliveira (2005), Henning (2010). In this perspective, we realize that there is not only a cause, but several factors together that cause this behavior, but we know that it is possible to reverse this situation with help from society, family and school.